2006
DOI: 10.1128/cvi.00191-06
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines with the MF59 Adjuvant Do Not Stimulate Antibody Responses against Squalene

Abstract: Squalene is a naturally occurring oil which has been used in the development of vaccine adjuvants, such as the oil-in-water emulsion MF59. In past years, by use of noncontrolled and nonvalidated assays, a claim was made that antisqualene antibodies were detectable in the sera of individuals with the so-called Gulf War syndrome. Using a validated enzyme-linked immunosorbent assay for the quantitation of immunoglobulin G (IgG) and IgM antibodies against squalene, we demonstrated that antisqualene antibodies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 14 publications
1
38
0
3
Order By: Relevance
“…Najpoznatiji primer su teze o pogubnim efektima skvalena i timerosala (etil-žive) koji se nalaze u pojedinim vakcinama u svojstvu adjuvansa, odnosno konzervansa. Iako nam raspoloživ prostor ovog rada ne dozvoljava zadovoljavajuće potpunu analizu bezbednosti ovih komponenti, uputno je pomenuti da je skvalen fiziološki metabolit koji se u ljudskom telu dnevno stvara u većoj količini od one koja se može naći u bilo kojoj vakcini [13], te da antitela na skvalen nisu nađena u većoj meri kod osoba koje su primile skvalen u svojstvu adjuvansa u odnosu na kontrolne osobe [14]; količina žive u jednoj dozi vakcine koja sadrži timerosal, pak, grubo odgovara količini u jednom obroku ribe ulovljene u prosečno zagađenom području 1 [15]. Iz naučnih studija koje su do sada tragale za dokazima toksičnosti skvalena i timerosala ne može se izvući zaključak da merljiv štetni efekat postoji [16], premda je, u skladu sa principom predostrožnosti, u mnogim zemljama, naročito u SAD, prisutna težnja da se prednost dâ vakcinama bez ovih sastojaka.…”
Section: Adjuvansi I Pomoćne Komponenteunclassified
“…Najpoznatiji primer su teze o pogubnim efektima skvalena i timerosala (etil-žive) koji se nalaze u pojedinim vakcinama u svojstvu adjuvansa, odnosno konzervansa. Iako nam raspoloživ prostor ovog rada ne dozvoljava zadovoljavajuće potpunu analizu bezbednosti ovih komponenti, uputno je pomenuti da je skvalen fiziološki metabolit koji se u ljudskom telu dnevno stvara u većoj količini od one koja se može naći u bilo kojoj vakcini [13], te da antitela na skvalen nisu nađena u većoj meri kod osoba koje su primile skvalen u svojstvu adjuvansa u odnosu na kontrolne osobe [14]; količina žive u jednoj dozi vakcine koja sadrži timerosal, pak, grubo odgovara količini u jednom obroku ribe ulovljene u prosečno zagađenom području 1 [15]. Iz naučnih studija koje su do sada tragale za dokazima toksičnosti skvalena i timerosala ne može se izvući zaključak da merljiv štetni efekat postoji [16], premda je, u skladu sa principom predostrožnosti, u mnogim zemljama, naročito u SAD, prisutna težnja da se prednost dâ vakcinama bez ovih sastojaka.…”
Section: Adjuvansi I Pomoćne Komponenteunclassified
“…51 As previously pointed out, squalene is a biodegradable and biocompatible compound; in humans, it is precursor of cholesterol and play an important role in the synthesis of steroid hormones and Vitamin D; moreover, it has been demonstrated that the administration of MF59 TM -adjuvanted subunit influenza vaccines did not elicit a specific humoral response against squalene. [52][53][54] In 1997, the first MF59™ adjuvanted vaccine has been licensed for human use and registered in Europe for use in adults ≥ 65 y old for seasonal influenza vaccine and furthermore, consistent preclinical, clinical and post-marketing experience on the use of MF59 TM adjuvanted pandemic vaccine has been accumulated in the last decade both against avian A(H5N1) and A(H1N1) pdm 09.…”
Section: Tm -Adjuvanted Vaccinesmentioning
confidence: 99%
“…However, the species-and antigen-dependent variation in immunogenicity enhancement by MF59 appears to be a deficiency of this adjuvant system [15,138]. MF59 does not seem to induce significant side effects compared with vaccines without MF59 in healthy adults [137,139]. Recent studies show that MF59 is associated with more reports of injection site pain and tenderness (local reactogenicity) relative to a non-adjuvanted flu vaccine in children and young adults [140,141].…”
Section: Emulsionsmentioning
confidence: 99%
“…CEL-1000 (18-mer) is an analogue of peptide G (a peptide from human MHCII beta chain, aa [135][136][137][138][139][140][141][142][143][144][145][146][147][148][149], which is known to enhance immune responses of other immunogenic peptides. They can be conjugated to HIV (HGP-30) and malaria peptides as potential vaccines.…”
Section: Specific Peptides/proteinsmentioning
confidence: 99%